Archives and special collections as sites of contestation - Kandiuk, Mary, 1956- (Library Juice Press, 2020)
"Explores the reinterpretation and resituating of archives and special collections held by libraries, examines the development and stewardship of archives and special collections within a social justice framework, and describes the use of critical practice by libraries and librarians to shape and negotiate the acquisition, cataloguing, promotion and use of archives and special collections"--